A novel customer knowledge management analysis model: With a case study in hospitality - Liu,X. (WIT Press, 2015)
© 2014 WIT Press. Customer knowledge management process with models can help managers to find the real value chain in business. This paper proposes a novel two-dimension customer knowledge management analysis model, which make customer knowledge more understandable and manageable. A case study is illustrated and shows the application of the CKM model in customer processes can lead to increased process performance.